A05 Longitudinal functional and connectivity changes during working memory performance in Huntington's disease: the image-HD study. (29th August 2012) - Georgiou-Karistianis, N; Stout, J; Poudel, G; Gray, M; Dominguez, J; Churchyard, A; Chua, P; Egan, G
Abstract : Background: Functional changes in the brain have been shown in both premanifest Huntington's disease (pre-HD) and symptomatic HD (symp-HD) individuals during both cognitive and motor task performance. Aims: One aim of the IMAGE-HD study is to improve understanding of functional brain reorganisation during pre-HD via functional MRI (fMRI). Here, we report on the longitudinal investigation of working memory using a modified version of the N-BACK paradigm consisting of 0-BACK, 1-BACK, and 2-BACK conditions. We report only on 0-BACK and 1-BACK for this investigation. Methods: Participants were recruited as part of IMAGE-HD and were assessed at baseline and 18 months. Data for a total of 70 participants was included in the analyses (19 symp-HD, 28 pre-HD and 23 controls). Results: Behavioural results revealed a significant difference in the rate of change in per cent correct between controls and symp-HD participants (0-BACK only) and shorter response times for controls (0-BACK and 1-BACK). FMRI showed decreased BOLD activations at 18 months for controls in frontal and parietal regions and only within the parietal region for symp-HD. There was significantly increased BOLD activation across a number of cortical and subcortical regions at 18 months in the pre-HD group. Pair-wise correlation based functional connectivity analysis was used to evaluate synchronicity in neuronal activity between various cortical and sub-cortical regions that showed robust activation during 1-BACK performance (ie, prefrontal, posterior, parietal, caudate, and cingulate areas). We found a significant longitudinal reduction in connectivity only for the pre-HD group, specifically between pre-frontal and parietal regions with anterior cingulate. Conclusions: These findings demonstrate that functional and connectivity changes occur well before disease onset. The increased functional activation, taken together with decreased functional connectivity, may offer new and important insights on brain compensation during premanifest stages of the disease.